PERAN PEMERINTAH GAMPONG DALAM MENGOPTIMALKAN PROGRAM POSYANDU - Zuhrizal Fadhly; Rahmayana Rahmayana (Universitas Teuku Umar, 2018)
This study aims to analyze the extent of the role of the Peunaga Rayeuk Village Government in Optimizing the Posyandu Program, analyze what are the supporting factors and inhibiting factors and analyze the actions taken in dealing with communities that are less participatory in the posyandu program. This study uses qualitative methods with descriptive analysis research types. To obtain comprehensive data, informants in this study were village government officials, posyandu cadres, midwives and the community. Data collection techniques are carried out by observation, interviews and documentation. Data analysis techniques using descriptive analysis techniques with a qualitative approach that describes the results of the study as it is.The results of this study indicate that the role of the village government in optimizing the Posyandu program is not optimal. This can be seen from the unavailability of a comfortable place for the community to obtain services, because the posyandu building is still used with kindergarten children and the services provided are not in accordance with the SOP. However, in terms of handling the community, namely infants / toddlers who are affected by malnutrition, the level of responsiveness of the gampong government, cadres and midwives are very good and very helpful to the community. The gampong government also conducted socialization, healthy baby competitions, giving PMT as well as absent community visits to posyandu, which were conducted to increase community participation. The supporting factors in optimizing the posyandu program are very much one of them, good cooperation between the gampong government, cadres and midwives and the gampong community in running the posyandu program. Meanwhile, the inhibiting factors are a lack of public awareness, a mindset that is not yet developed and a sense of laziness in the community that makes them reluctant to bring their children to the posyandu and uncomfortable service places. Keywords: Role, gampong government, optimal, posyandu.